Pengaruh Kualitas Produk Terhadap Kepuasan, Reputasi Merek Dan Loyalitas Konsumen Jamu Tolak Angin Pt. Sido Muncul - Budi Hermawan (Universitas Airlangga, 2011)
One of the key factor that PT Sido Muncul concerns about its Jamu Tolak Angin is the customer loyalty. The increase number of loyal customers can be considered as the success of the company’s product amidst the competition. This research is conducted to find out whether the product’s quality influences the customer loyalty through customer satisfaction and brand reputation of the PT Sido Muncul’s Jamu Tolak Angin brand. This research is conducted to retest the model proposed by Fred Selnes (1993), by using the Structural Equation Model (SEM). The sample of this research is 200 persons, collected by judgment sampling. The result of this research shows that customer loyalty is influenced by product quality, customer satisfaction, and brand reputation. Product quality influences customer loyalty through customer satisfaction and brand reputation. The model’s test of this research shows Chi-Square=65.81 (P=0.00026), RMSEA=0.071, GFI=0.94, dan AGFI=0.90. Product quality influences customer loyalty through customer satisfaction and brand reputation by 0.26 and it influences customer loyalty through brand reputation by 0.46. This research shows that good quality product will lead to the increase of customer loyalty and brand reputation of the PT Sido Muncul’s Jamu Tolak Angin brand. Loyal customers are directly influenced by PT Sido Muncul’s Jamu brand, while customer satisfaction doesn’t directly influence customer loyalty. When choosing which jamu product to consume, the customers don’t necessarily choose the product based on the satisfaction of past use but on the brand reputation. Customers think that the jamu brand that has good reputation is suitable for continuous use. This is because customers view jamu as traditional medicine, so the selection should be based on those products who have reliable brand reputation. This result shows that the PT Sido Muncul’s Jamu Tolak Angin brand reputation that has been formed may strengthen the product quality’s influence on creating customer loyalty.